Diseño de un aplicativo que integre la planeación de la demanda y el manejo de inventarios para una empresa del sector de papel (2019)
Planning and integrating supply chain links is critical to achieving alignment between demand, inventory management and purchasing plan, in order to achieve the business objectives proposed by companies, improve profitability , generate results from strategies established by the company and improve the responsiveness of the different processes of the company to the requirements of the market, however, Duopapel lacks an integrated planning of the chain of supply since the planning of your demand is not structured, inventory management does not fully meet the needs of customers and the storage of your products, collection times for the arrival and departure of orders are not which means that demand is not fully met, leading to cost overruns and consumer dissatisfaction. As a solution to these problems and using forecasts, heuristics, indicators, the Pareto diagram and a master key, an application has been designed that effectively integrates and implements a model of demand planning, purchasing and inventories in the management of this company in the paper sector, within a twelve-month planning horizon, that allows to meet the demand and reduce inventory costs, generating results within the expected requirements of time, managing to meet standards where risks in the supply chain are reduced and the performance performance of the supply chain is optimized. In addition, to verify its effectiveness, a comparison of the proposed model against the current policy is made in order to verify the correct performance of the proposal.